Coleta de resíduos sólidos domiciliares em local de entrega obrigatória: aspectos de custos e opinião dos usuários - Souza, Edson Marcondes de (Universidade Federal de São Carlos, 2005)
This work presents a comparison between conventional solid waste collection, also known as door to-door collection which is used by most of the Brazilian s municipalities and the Mandatory Drop-Off Waste Collection At Specific Sites (CLEO), to where the residents must transport their domestic solid waste to be collected. Literature points to the Mandatory Drop-Off (CLEO) as likely to have the lowest cost in the solid waste system. Also, the paper proposes to compare this type of collection with the door-to-door collection. And in addition, to find out the residents opinion about this type of collection, a survey was conducted with the residents of a street segment in Bebedouro-SP, where a drop-off collection is currently made at specific sites, but not in a mandatory way. The survey points that the collection at specific points is 10 to 30 per cent less expensive than the door-to-door collection. (If crew and vehicles are taken in consideration) Bebedouro/SP s survey shows that 75% of respondents are involved and know about the collection of solid waste services. Most of residents that live around main street approved the way that collection and disposal are made, at a central island. However, 60% do not want a container in the curbside of their front house. Another important issue that the respondents declared is their disposition to make a certain sacrifice , like to walk a lot a distance to dispose their solid waste in order to pay their Town s taxes at a discount rate.
Keywords: Resíduos sólidos; Coleta de resíduos; Custos comparados; Coleta em local de entrega obrigatória; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::RESIDUOS SOLIDOS, DOMESTICOS E INDUSTRIAIS